Analisis dan Perancangan Aplikasi E-Voting untuk Pemilihan Mahasiswa berkarakter NICE: Studi Kasus di STT Terpadu Nurul Fikri - ; Zaki Imaduddin (Jurnal Informatika Terpadu, 2017)
E-Voting is an online or digital candidate selection method. This method makes it easy for users to make selections because it does not require a paper to become efficient and practical. Integrated STT Nurul Fikri has created an E-Voting system for the head of Bem and Deputy Bem. As time goes by, STT Nurul Fikri wants to develop this method by implementing the NICE program into the E-VOTING application. In this study, the authors discussed the process of analysis and design of the Android-based 5O-NICE E-Voting Application. The authors also collected data from observations and interviews as well as questionnaires. To do the test, the writer uses Blackbox Testing. The results obtained by the author from the analysis and design of this application are to add NICE values ​​to the Integrated STT student Nurul Fikri.